PERSPEKTIF GURU SEKOLAH DASAR TERHADAP PELAKSANAAN PILKADA DI KABUPATEN PANGANDARAN - Kurnia, Dadang (Mimbar Sekolah Dasar, 2016)
Pangandaran Regency is one of the regencies in Indonesia which youngest age as a result of the expansion area. Therefore, the local elections have been conducted in Pangandaran. Through this article, in which the data collection is done through observation and interviews. The researchers sought to examine the implementation of the local elections are based on the perspective of primary school teachers and other citizens. The study states that the organization of the elections took place safely, and there are about 239 475 votes or people who cast. Because this election is the first election and also in an atmosphere where community ownership seems to have its own area, the enthusiasm of citizens was so great.Keywords: election, Pangandaran, elementary school teacher perspective.Â